Object’s Movement Simulation with Air Drag: Aerodynamics Wall and Knuckle’s Effect - Sobar, Fiki Taufik Akbar (Indonesian Journal of Physics, 2024)
The drag force of air and objects can be analyzed using the Stokes or Quadratic, also known as the Newtonian method. In this research, a Newtonian model was created numerically in Python using a 4th order Runge-Kutta integrator. The integrator will solve the acceleration function experienced by the object when given air resistance into a position function. The object’s movement influenced by variation of drag’s coefficient will provide variations in the location of the aerodynamic wall, the condition when the object moves vertically downwards. The movement of an object that is influenced by air resistance under certain conditions will also experience a lifting force, due to the rotational orientation angle of the object. The movement of objects influenced by these two forces can be modeled as knuckle movement. The results obtained from the numerical solution of the two object conditions are then made into a simple application in the form of a GUI so that users can easily operate the object simulation. This research will be a solution for students to understand the motion of objects influenced by the drag forces that occur when taking classical mechanics courses.